PROFESSIONAL CONTEXTS AS A MEANS OF MONITORING THE PROCESS OF COMPETENCE FORMATION - Vera Tenishcheva; Yuliya Kuznetsova; Elena Tsyganko (Вестник Северо-Кавказского федерального университета)
The article examines the problem of monitoring the professional competence formation on the basis of integrative and contextual approach. The technology of professional contexts reconstruction in the business game as a means of monitoring competence formation process has been described. The results of componen t analysis of a business game in foreign language environment are enclosed.